Respuesta :

Answer:

x= 16

Step-by-step explanation:

combine multiplied terms into  a single fraction

[tex]\frac{1}{2} (x-4)=\frac{1}{3} (x+2)[/tex]

[tex]\frac{1(x-4)}{2} =\frac{1}{3} (x+2)[/tex]

Multiply by 1

[tex]\frac{1(x-4)}{2} =\frac{1}{3} (x+2)[/tex]

[tex]\frac{x-4}{2} =\frac{1}{3} (x+2)[/tex]

Combine multiplied term into a single fraction

[tex]\frac{x-4}{2} =\frac{1(x+2)}{3}[/tex]

Multiply by 1

[tex]\frac{x-4}{2} =\frac{x+2}{3}[/tex]

Multiply all terms by the same value to eliminate fraction denominators

[tex]6*\frac{x-4}{2} 6(\frac{x+2}{3} )[/tex]

cancel multiplied terms that are in the denominator

[tex]3(x-4)=2(x-2)[/tex]

Distribute

[tex]3x-12=2(x+2)[/tex]

Distribute

[tex]3x-12=2x+4[/tex]

Add 12 to both sides of the equation

[tex]3x-12+12=2x+4+12[/tex]

Simplify

[tex]3x=2x+16[/tex]

Subtract 2x from both sides of the equation

[tex]3x=2x=2x+16-2x[/tex]

Simplify

[tex]x=16[/tex]